CYP-450 isoenzymes catalyze the generation of hazardous aromatic amines after reaction with the azo dye Sudan III - Zanoni, Thalita Boldrin; Lizier, Thiago M. [UNESP]; Assis, Marilda das Dores; Zanoni, Maria Valnice Boldrin [UNESP]; De Oliveira, Danielle Palma (Elsevier, 2013)
This work describes the mutagenic response of Sudan III, an adulterant food dye, using Salmonella typhimurium assay and the generation of hazardous aromatic amines after different oxidation methods of this azo dye. For that, we used metabolic activation by S9, catalytic oxidation by ironporphyrin and electrochemistry oxidation in order to simulate endogenous oxidation conditions. The oxidation reactions promoted discoloration from 65% to 95% of Sudan III at 1×10-4molL-1 and generation of 7.6×10-7molL-1 to 0.31×10-4molL-1 of aniline, o-anisidine, 2-methoxi-5-methylaniline, 4-aminobiphenyl, 4,4'-oxydianiline; 4,4'-diaminodiphenylmethane and 2,6-dimethylaniline. The results were confirmed by LC-MS-MS experiments. We also correlate the mutagenic effects of Sudan III using S. typhimurium with the strain TA1535 in the presence of exogenous metabolic activation (S9) with the metabolization products of this compound. Our findings clearly indicate that aromatic amines are formed due to oxidative reactions that can be promoted by hepatic cells, after the ingestion of Sudan III. Considering that, the use of azo compounds as food dyestuffs should be carefully controlled. © 2013 Elsevier Ltd.
Keywords: Aromatic amines; Biomimetical models; Electrochemical oxidation; Ironporphyrins; Oxidative metabolism; Sudan dyes; 2 methoxy 5 methylaniline; 2,6 dimethylaniline; 4 biphenylamine; 4,4' diaminodiphenyl ether; 4,4' methylenedianiline; anisidine; aromatic amine; ironporphyrin; oil scarlet; porphyrin; unclassified drug; base pairing; catalysis; electrochemistry; frameshift mutation; liquid chromatography; mass spectrometry; metabolic activation; mutagenic activity; oxidation; Salmonella typhimurium